Tuberculosis Osteomyelitis Of Mandible With Pathological Fractures - Mitra, M.; Agrawal, K.; Mitra, S. K.; Pathak, I. C. (Indian Journal of Plastic Surgery, 1982)
A rare case of tuberculous osteomyelitis mandible with pathological fracture has been reported. The problems in diagnosis and principles of management have been highlighted. Accurate, repair of mucosal tear and longer period of immobilization are necessary.